Bounds for del pezzo surfaces of degree two. (4th August 2022) - Ghosh, Aritra; Kumar, Sumit; Mallesham, Kummari; Singh, Saurabh Kumar
Abstract: In this article, we obtain an upper bound for the number of integral points on del Pezzo surfaces of degree two.